Pengembangan Kompetensi Digital ASN di Badan Kepegawaian Daerah Kepulauan Riau: Strategi dan Tantangan Implementasi - Pebby Regita Sinaga; Bismar Arianto (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
The development of information and communication technology (ICT) has changed governance in Indonesia, driving digital transformation to improve public services, transparency, and accountability. In this context, the Regional Civil Service Agency (BKD) of the Riau Islands Province plays an important role in developing the digital competence of the State Civil Apparatus (ASN). This study aims to identify the strategies implemented by BKD in developing ASN digital competence and the challenges faced during implementation. The research method used is a qualitative approach with a case study design, involving in-depth observation interviews. The results of the study indicate that although various strategies have been implemented, challenges such as the digital literacy gap between generations, infrastructure constraints, and cultural resistance are still significant obstacles. Recommendations for improving the development of ASN digital competence include improving IT infrastructure, ongoing training programs, and strengthening regulations. This study is expected to provide an empirical overview and recommendations to accelerate digital transformation in the local government environment.